Life Cycle Assessment pada Solar Photovoltaics: Review - James Parulian Manurung; Mohamad Sidik Boedoyo (Jurnal Penelitian Sains Teknologi, 2025)
One of the most important needs of everyone is electricity, from households to industries. In recent years, electricity sources are still dependent on fossil fuels where energy sources from fossils will continue to decrease for several years to come. This condition requires us to look for renewable energy to support our daily lives. One of the well-known sources of renewable energy is from the sun, which can be utilized by energy conversion devices called solar cells. Countries located on the equator such as Indonesia are blessed with abundant sunshine throughout the year. Therefore, the application of solar cells with photovoltaic (PV) technology utilizes sunlight to be converted into electricity. Although this technology is emerging very quickly, there are still drawbacks due to the current use of PV technology, its environmental impact and economic feasibility. Life cycle assessment is a method or way to analyze and evaluate the sustainability of a PV system and its environmental impact. This paper presents a literature study of 'PV systems from cradle to gate', starting with material selection (from first generation and possibly fourth generation), manufacturing process, implementation, and ending with after-life effects. of the PV module. 'The result of this study is to show insight into the application of PV systems in Indonesia, starting from the best materials, the best application methods, energy return times, and finally the possibility of recycling PV materials after their lifetime. starting with the choice of material (from the first generation and possibly the fourth generation), the manufacturing process, implementation, and ending with the life effect of the PV module